PERAN GURU DALAM MENANAMKAN SIKAP TOLERANSI KEPADA SISWA KELAS IV MI MA’HAD AL-ZAYTUN - Kholifah Al Marah Hafidzhoh; Dede Indra Setiabudi; Dadan Mardani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The research is motivated by the importance of instilling an attitude of tolerance in elementary school students, the reality in the field shows that even though students have known tolerance, problems such as egocentric attitudes are still found in the classroom, Therefore, this study aims to describe the role of teachers and their application in instilling an attitude of tolerance to grade IV students of Madrasah Ibtidaiyah Ma'had Al-Zaytun. This study uses a qualitative approach with a descriptive type of research. The subjects of the study were teachers and fourth grade students at Madrasah Ibtidaiyah Ma'had Al-Zaytun, Data was obtained through interviews, observations, and documentation. To strengthen the analysis, this study refers to James A. Banks' multicultural education theory and Gordon Allport's contact hypothesis which is relevant to instilling the value of tolerance through equality in opinion. The results of the study show that teachers have a central role in instilling tolerance through various approaches. As a learning resource and educator, teachers emphasize the importance of respecting differences and respecting the opinions of others. As facilitators, teachers create group discussion spaces to get students used to working together and resolving differences democratically. In their role as classroom managers, teachers apply discipline rules, as well as an educational reward and punishment system. Keywords: Teacher’s role, tolerance attitude, students.